The use of hydrotherapy in the first stage of labour: A systematic review and meta-analysis - DEMİRGÖZ BAL, MELTEM (My University, 2023)
Aim: To explore the effect of hydrotherapy applied in the first stage of labour on the health of mother and newborn. Methods: This systematic review and meta-analysis was carried out by following PRISMA. The studies were obtained by scanning EBSCO, PubMed, Science Direct, Ovid, Web of Science and Scopus electronic databases. Twenty studies published between 2013 and 2023 were included. Results: The total sample size of the studies was 8254 (hydrotherapy: 2953, control: 5301). Meta-analyses showed that the perception of pain decreased, comfort level and vaginal birth rate were higher and assisted vaginal birth rate and APGAR scores in the first minute were lower in women who underwent hydrotherapy. There was no difference between groups in terms of the duration of the first and second stage of labour, episiotomy, perineal trauma, intrapartum and postpartum bleeding amounts, use of pain medication and labour augmentations, APGAR scores in the fifth minute, positive neonatal bacterial culture and neonatal intensive care unit need. Conclusion: This study revealed that the results that hydrotherapy decreased the perception of pain and assisted birth, increased the rate of vaginal birth and comfort level and did not adversely affect the health of the mother and baby during the birth process.
Keywords: hydrotherapy; intrapartum care; labour; midwifery; nursing; women's health